Moisture dependent postharvest physical and textural characteristics of brown sesame seed (var. TMV-4): MOISTURE DEPENDENT POSTHARVEST PHYSICAL AND TEXTURAL CHARACTERISTICS OF SESAME - M R MANIKANTAN; T ARUL SELVAM; RAJIV SHARMA; PANKAJ KUMAR; T SEERANGURAYAR (Journal of Oilseeds Research, 2014)
Physical and textural characteristics are important in design and manufacturing of harvest and post harvest machines. Some postharvest physical and textural characteristics of brown sesame seed (var. TMV-4) were determined as a function of moisture content in the range of 4.3 per cent to 20 per cent (d.b). The axial dimensions, geometric mean diameter, surface area, volume, sphericity and aspect ratio were found to be increasing linearly for all studied moisture levels. Furthermore, the thousand seed mass, true density, porosity and the angle of repose also increased linearly whereas, bulk density decreased linearly with the increase of moisture content under study. The results showed that the static coefficient of friction on four different surfaces of plywood, mild steel, galvanized iron and glass also increased linearly for all level of moisture. The initial cracking force, average rupture force and average rupture energy decreased linearly with increased moisture content of 4.3 to 20 per cent (d.b.).